Proceedings of the 2016 International Conference on Artificial Intelligence: Technologies and Applications 2016
DOI: 10.2991/icaita-16.2016.49
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Realistic Fluid Re-simulation

Abstract: Abstract-Re-simulating a 3D fluid result from video while retaining and rendering details is significant in practice, which still remains a difficult task in spite of rapid advancements in this field during the last two decades. Physically driven models can be easily extended to handle fluid, yet they are unable to preserve surface details like breaking waves without the expense of increasing particle densities. This paper proposes a hybrid particle Lattice Boltzmann Model for Shallow Waters (LBMSW) coupling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…They also found that aggregating the input features with statistical functions over temporal windows is instrumental in obtaining better results. In [46], the authors perform multi-task learning via deep recurrent neural networks to predict the next position and travel mode in a sequence of GPS data points. They show that using deep learning allows for a significant improvement over traditional "shallow" models, such as Gaussian processes and Hidden Markov Models.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that aggregating the input features with statistical functions over temporal windows is instrumental in obtaining better results. In [46], the authors perform multi-task learning via deep recurrent neural networks to predict the next position and travel mode in a sequence of GPS data points. They show that using deep learning allows for a significant improvement over traditional "shallow" models, such as Gaussian processes and Hidden Markov Models.…”
Section: Introductionmentioning
confidence: 99%